Quadriceps EMG muscle activation during accurate soccer instep kicking - Scurra, J. C.; Abbotta, V.; Ballb, N. (Journal of Sports Sciences, 2011)
Six competitive soccer players were recruited to examine EMG activation in three quadriceps muscles during a kicking accuracy task. Participants performed three maximum instep place kicks of a stationary ball, 11 m perpendicular from the centre of the goal line towards targets (0.75 m2) in the four corners of the goal. Surface EMG of the vastus lateralis, vastus medialis, and rectus femoris of the kicking leg was normalized and averaged across all participants to compare between muscles, targets, and the phase of the kick. Although no significant difference were observed between muscles or kick phases, kicks to the right targets produced significantly greater muscle activity than those towards the left targets (P < 0.01). In addition, kicks towards the top right target demonstrated significantly greater muscle activity than towards the top and bottom left (P < 0.01). Under accurate soccer shooting conditions, kicks aimed to the top right corner of the goal demonstrated a higher level of quadriceps muscle activation than those towards the other corners.